Possible efficacy of hydroxychloroquine on accelerated nodulosis during methotrexate therapy for rheumatoid arthritis [1] (1993)
This letter shows some possible efficacy of hydroxychloroquine on accelerated nodulosis during methotrexate therapy for rheumatoid arthritis, Arthritis, Rheumatoid/complications,Arthritis, Rheumatoid/drug therapy; Humans; Hydroxychloroquine/therapeutic use; Methotrexate/adverse effect, Methotrexate/therapeutic use; Rheumatoid Nodule/drug therapy